Research on the insured amount of disaster housing insurance based on particle swarm optimization algorithm - Wang, Hongkun; Niu, Yifan (Transactions on Economics, Business and Management Research, 2024)
Due to the impact of global climate change, the frequent occurrence of extreme weather has had a huge impact on local economic development. Insurance can reduce risks and alleviate the burden on individuals or businesses. Based on the analysis of the profit model of insurance companies, it is found that profit is related to the company's revenue and expenses. Therefore, this article has defined the objective function, decision variables, and constraints for profit. This article conducted a detailed analysis of the relevant conditions between income and expenditure, analyzed the frequency of natural disasters worldwide, and predicted that there may still be many natural disasters in these two regions in the next five years using time series analysis. This article selected China and the United States as the two continents. Reuse particle swarm optimization algorithm to determine the highest and lowest insurance amounts for China and the United States, and develop detailed insurance strategies within the range of amount indicators to reduce losses.